THREE-DIMENSIONAL HYDRODYNAMICAL MODELING OF MASS TRANSFER IN THE CLOSE BINARY SYSTEM LYR WITH AN ACCRETOR WIND.III - Nazarenko, V. V.; Glazunova, L. V. (Одеські астрономічні публікації, 2007)
The present paper continues our work on numerical modelling of formation of the accretion disc in CBS β Lyrae taking into account the stellar wind of the accretor. On having used methods of additional reduction of numerical viscosity, as well as different variants of the stellar wind and terms of its displacement out of the orbital plane while forming a disc, we defined the disc parameters close to the observational ones, and also jet like structures, where gas velocity equals to the velocity of the accretor’s stellar wind.